Photosysnthetic pigment and genetic differences between two Southern Ocean morphotypes of Emiliania Huxleyi (Haptophyta) - Cook, SS; Whittock, LD; Simon Wright; Gustaaf Hallegraeff (2011)
The widespread coccolithophorid Emiliania huxleyi (Lohmann) W. W. Hay et H. Mohler plays a pivotal role in the carbon pump and is known to exhibit significant morphological, genetic, and physiological diversity. In this study, we compared photosynthetic pigments and morphology of triplicate strains of Southern Ocean types A and B/C. The two morphotypes differed in width of coccolith distal shield elements (0.11–0.24 μm, type A; 0.06–0.12 μm, type B/C) and morphology of distal shield central area (grill of curved rods in type A; thin plain plate in type B/C) and showed differences in carotenoid composition. The mean 19′-hexanoyloxyfucoxanthin (Hex):chl a ratio in type B/C was >1, whereas the type A ratio was <1. The Hex:fucoxanthin (fuc) ratio for type B/C was 11 times greater than that for type A, and the proportion of fuc in type A was 6 times higher than that in type B/C. The fuc derivative 4-keto-19′-hexanoyloxyfucoxanthin (4-keto-hex) was present in type A but undetected in B/C. DNA sequencing of tuf A distinguished morphotypes A, B/C (indistinguishable from B), and R, while little variation was observed within morphotypes. Thirty single nucleotide polymorphisms were identified in the 710 bp tuf A sequence, of which 10 alleles were unique to B/C and B morphotypes, seven alleles were unique to type A, and six alleles were unique to type R. We propose that the morphologically, physiologically, and genetically distinct Southern Ocean type B/C sensu Young et al. (2003) be classified as E. huxleyi var. aurorae var. nov. S. S. Cook et Hallegr.